Thinking Intermediality in Mexico through Artistic Input - González Aktories, Susana; Giovine Yáñez, María (Intermédialités / Intermediality, 2017)
By highlighting certain paradigmatic moments and protagonists in Mexican contemporary art that reach back to the second half of the last century and continue until today, this article aims to show the undeniable “intermedial turn” that has become foundational not only for understanding current artistic movements in Mexico, but also for Mexican academia, where critics have only gradually started to recognize how an intermedial perspective may help them understand and analyze artistic proposals that can no longer be discussed from a strictly mono-disciplinary standpoint. Contributions by emblematic artists such as Mathias Goeritz, Felipe Ehrenberg, and Ulises Carrión, who have used words, images, and sound elements to broaden artistic boundaries in new and surprising ways, have been echoed and problematized in novel forms by contemporary visual artists such as Carlos Amorales and Jorge Méndez Blake as well as media artists Rafael Lozano Hemmer and Eugenio Tisselli, some of whom are also valuable interlocutors in matters of intermediality as they continue to critically theorize and sharply reflect on these types of practices.